PKM KERAJINAN KERAMIK ANEKA PRODUK OLAHAN TANAH LIAT SIKU BALI HANDYCRAFT DI BALI - I Gusti Ayu Ratih Permata Dewi; Putu Yudha Asteria Putri; I Gde Agung Wira Pertama (Universitas Kadiri, 2020)
ABSTRACTCraft is an object of human art that is related to hand skills. Besides having aesthetic value,the shape of the craft has economic value. One of the handicrafts in Bali is ceramics. Theseceramics are usually used as souvenirs for tourists who come to Bali. The target audienceof this community service program is the